Assessing sustainability opportunities for circular business models. (29th December 2021) - Averina, Elizaveta; Frishammar, Johan; Parida, Vinit
Abstract: As the unfolding climate crisis escalates, incumbent manufacturing companies are increasingly sensing and seizing sustainability opportunities—ideas that help to generate value in a more sustainable way than existing alternatives. Prior literature has underscored the importance of opportunity recognition and has theorized various types of circular business models to address sustainability in practice. However, there is a knowledge gap regarding the step in between: undertaking an assessment that provides a foundation for subsequently pursuing a circular business model. Based on a multiple case study of four innovation projects pursuing sustainability, this article identifies capability assessment, ecosystem alignment, and value‐capture viability as key dimensions in evaluating sustainability opportunities prior to circular business model design and development. These insights are aggregated into a framework that allows companies to conduct a systematic assessment of sustainability opportunities in practice. The framework provides new theoretical implications for the literature on circular economy and business model innovation, and it offers hands‐on advice for management practice.